Finance and Development, September 2005. (Finance and Development; Finance and Development ;, 2005)
This paper explores why increased aid flows require economic policymakers to confront some specific issues. Ensuring that increased aid promotes growth and reduces poverty is certainly the most important task. Empirical studies offer only mild support for aid-boosting growth. However, one study suggests that once one excludes the aid flows aimed at political and humanitarian goals, a positive net effect is observed for the remaining aid focused on economic objectives. This paper also outlines the roles to be played by development partners for making the aid being properly utilized for boosting growth.